Entre o dito e o não dito: o hiato entre a psicanálise e o direito em relação ao abuso sexual infantil. - Leite, Simone Matos Lacerda (2019)
This paper aims to investigate the points of encounter and mismatch between the areas of psychoanalysis and law, specifically in relation to the theme of child sexual abuse. From a brief retrospective we seek to investigate the theme of child sexual abuse, throughout the development of human history, seeking to understand the various moments in which this practice was present in societies. We seek to highlight the current moment, when new technologies, driven by the internet, pose an additional danger to the vulnerability to which children are exposed, due to the easy access of abusers as opposed to the legal resources available to suppress and punish such practices. We analyze the various definitions of child sexual abuse brought by leading scholars in the area and the institutions that propose to address the issue. We investigated how the theme is approached by Psychoanalysis, based on basic concepts of its theoretical scope, such as trauma and psychic reality, highlighting the tensions that are evident when these terms are taken by legal action. We brought a historical overview of the child, under the lens of law, emphasizing the different ways in which childhood was seen over time and how the law has been positioned in relation to child sexual abuse. From its theoretical devices, we try to bring an analysis of the way of acting used in dealing with the listed theme. We verified, through the bibliographical research, that the original point from which each of the disciplines comes, are distinct from each other, as well as their methodological and procedural devices. We seek to emphasize that the meeting between the disciplines will inevitably happen, but for now, still under a lot of tension, perhaps driven by lack of understanding, of each other, of their objects of interest, that is, the psychic subject and the subject of rights. We see the possibility of this meeting happen, in fact, as a dialogue, mediated by the human subject, from an interdisciplinary view.